THE DESCRIPTIVE ANALYSIS ON TEACHERS’ STRATEGY IN TEACHING ENGLISH WRITING OF RECOUNT TEXT AT THE EIGHTH GRADE OF UPTD SMP NEGERI 2 MANDREHE BARAT IN 2022/2023 - Bonavide Kristiani Gulo; Kristof M.E. Telaumbanua; Hidayati Daeli; Adieli Laoli (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2023)
This research aims to know the strategies of teachers in teaching writing recount text at the 8th grade of UPTD SMP Negeri 2 Mandrehe Barat. This research uses qualitative methods using an inductive approach. The necessary data is collected through observations and interviews. Participants in the research were two English teachers and at the 8th grade of UPTD SMP Negeri 2 Mandrehe Barat of 42 students. Results from data analysis show that English teachers use strategies in teaching writing, the first teacher uses two types of strategies: discussion strategy, and question-and-answer (Q&A) strategy, while the second teacher uses discussion strategy. Meanwhile, the results of research conducted to students through interviews showed that both teachers have used the above strategy. From the results of observations and interviews of both teachers, they used several strategies such as discussion strategy, question-and-answer strategy, with the aim of making students easy to understand the material and active in the learning process. This strategy is used because the discussion strategy is one of the most effective teaching strategies to encourage interaction between teachers and students while the question and answer strategy is an effective way for teachers to examine students' understanding of a subject.